Mental health and psychotropic medication trends during the COVID-19 pandemic in a middle eastern population: A systematic analysis of electronic medical records from Qatar - Kholoud, Bastaki (2025)
BackgroundThe COVID-19 pandemic has had a detrimental impact on the mental health of populations. We aimed in this examines the impact of the COVID-19 pandemic on the prevalence and treatment of mental health disorders (MHDs), with a specific focus on patterns of psychotropic medication prescriptions in Qatar. It provides critical insights into the dynamics of mental healthcare during global crises. MethodsIn this retrospective observational study, we conducted an analysis of data derived from 267,116 outpatients attending Mental Health Services (MHS) in Qatar between 2019 and 2022. The study focused on trends in outpatient visits and psychotropic medication prescriptions. ResultsA significant increase of 56.6 % in MHS outpatient visits was observed in 2022 compared to pre-pandemic levels, indicating heightened utilization of mental health services. Depression and anxiety disorders were predominant, reflecting global patterns. Antidepressant prescriptions rose by approximately 40 %, highlighting increased psychological distress. ConclusionThe findings emphasize the necessity for tailored therapeutic protocols and robust mental healthcare infrastructures to address the rising burden of MHDs during crises. Integrating genetic predispositions with prescription trend analyses offers promise for future interventions, contributing to a resilient mental healthcare ecosystem capable of adapting to evolving needs in crisis contexts and beyond.